The National Broadband Network Brownfields Debate - Valuing FTTN and FTTP. - Ferrers, Richard Anthony (Journal of Telecommunications and the Digital Economy, 2016)
This paper analyses the value of FTTN and FTTP along financial and non-financial dimensions. It reports on an open, public, dynamic ‘value model’ of FTTN and FTTP, and showcases two visual tools to enable assessment of their multiple, competing, emerging and slippery ‘value dimensions’. The paper reports and compares empirically-derived FTTN and FTTP value dimensions from recent Ministerial Speeches at CommsDay Summit 2016 and Government expert reports with the value model.